Upaya Meningkatkan Hasil Belajar Senam Lantai Guling Depan melalui Permainan Siswa Kelas IV.C SD Negeri 10 Cakranegara - Gunawan, I Made (Lembaga Yasin AlSys, 2022)
The goal to be achieved in this research is to improve the learning of forward roll floor exercise through games for fourth grade students at SD Negeri 10 Cakranegara for the 2021/2022 Academic Year. The results of the research and discussion that have been described in the previous chapter, it can be concluded that the increase in learning outcomes of forward roll floor exercise through a modified game approach is characterized by an increase in the average value of students. The average value of students in the initial conditions was 73.77 with a completeness percentage of 61.454%. This condition experienced an increase in the average value of students in cycle I, which was equal to 77.54 and the percentage of completeness was 80.77%. However, this increase still has not reached the target previously set. Then after continuing to cycle II the average value of the students' forward roll floor exercise ability again increased by 82.27 with a completeness percentage of 82.27%. This shows that the targets previously set have been achieved so that the research was stopped in cycle II. The learning process of forward roll floor exercise through a modified game approach is dynamic and fun and the results of observations of the teacher during learning also increase in every meeting.